2015
DOI: 10.15386/cjmed-396
|View full text |Cite
|
Sign up to set email alerts
|

The surgical treatment of inguinal hernia using the laparoscopic totally extra-peritoneal (TEP) technique

Abstract: The surgical repair of inguinal hernia represents one of the most frequent procedures used in general surgery. The new surgical techniques are simpler, with a lower morbidity and recurrence of less than 2%. The laparoscopic totally extra-peritoneal (TEP) technique is contraindicated in complicated hernias (occlusion, incarceration) and in voluminous inguino-scrotal hernias.PurposeThe evaluation of the TEP technique, of the risk factors and of the postoperative results on the group of patients who have undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
1
0
2
Order By: Relevance
“…This probably explains the positive correlation between operative time. Studies have demonstrated preference of laparoscopic methods over open techniques, mainly due to the possibility to reach the contralateral side through the same incision 5 , 20 , 22 , 34 . Among laparoscopic approach, the prospective randomized trial of 60 patients of Sharma et.…”
Section: Discussionmentioning
confidence: 99%
“…This probably explains the positive correlation between operative time. Studies have demonstrated preference of laparoscopic methods over open techniques, mainly due to the possibility to reach the contralateral side through the same incision 5 , 20 , 22 , 34 . Among laparoscopic approach, the prospective randomized trial of 60 patients of Sharma et.…”
Section: Discussionmentioning
confidence: 99%
“…Разделяем мнение ряда исследователей, что лапароскопические операции при паховой грыже имеют преимущества перед открытыми, в частности благодаря возможности визуальной интраабдоминальной оценки паховой области на стороне противоположной грыже [12,13]. Выводы 1.…”
Section: таблица 3 -результаты раннего послеоперационного периодаunclassified
“…Der aus Körpergröße und Gewicht errechnete BMI-Mittelwert für das Gesamtkollektiv von 26,8 kg/m² liegt höher als in vergleichbaren Kollektiven, die niedrigere Mittelwerte von beispielsweise 23,8 und 24,9 kg/m² aufweisen(Bansal et al 2013;Mihaileanu et al 2015).…”
unclassified